Molecular Determinants of SARS-CoV-2 Variants - Banerjee, Arinjay (Trends Microbiol, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) evolution is expected, given the nature of virus replication. Selection and establishment of variants in the human population depend on viral fitness and on molecular and immunological selection pressures. Here we discuss how mechanisms of replication and recombination may contribute to the emergence of current and future variants of SARS-CoV-2.